Growth and distribution - Foley, Duncan K. (Harvard University Press, 2019)
This comprehensive book on the theory, measurement, and history of economic growth presents Classical and Keynesian in parallel with Neoclassical approaches, and the new variant, neoliberal capitalism. It covers growth theory, tools of intertemporal economic analysis, money and growth, technological change, the 2008 financial crisis, the rise of inequality, along with technological change, land and resource limitations, and climate change.